Associations between different forms of gastro-oesophageal reflux disease - El-Serag, H (1997)
Abstract  Aims—To study the epidemiology and natural history of gastro-oesophageal reflux disease (GORD).  Methods—Retrospective cohort study involving all 172 hospitals of the Department of Veterans Affairs. A total of 194 527 patients with GORD were followed between 1981 and 1994. Distribution of oesophagitis, oesophageal ulcer, oesophageal stricture, strictured hiatus hernia, hiatus hernia, and pyrosis by age, sex, and ethnicity were determined. The comorbid occurrence of various forms of GORD in identical patients was analysed by an age and race standardised morbidity ratio. The population of all hospitalised veterans was used for comparison.  Results—Severe forms of GORD associated with oesophageal erosions, ulcers, or strictures, affected elderly, white, male patients more often than their corresponding opposite demographic group. All forms of GORD clustered in the same patient population; on average, any form of GORD was 10 times more likely to occur in a patient with another form of GORD than without. The highest morbidity ratio (22) was found in oesophageal ulcer and stricture. About one third of all patients with oesophageal erosions, ulcers, or strictures also had hiatus hernia; 46% of patients with hiatus hernia were diagnosed as having other forms of GORD. While one third of all oesophageal strictures appeared in patients without other forms of GORD diagnosed at any time, oesophageal ulcers were always associated with some other form of GORD. No clear cut progression in different forms of GORD was found.  Conclusions—Older age, male sex, and white ethnicity are risk factors in the development of severe forms of GORD. The most severe grade of GORD is reached at the onset of the disease.    Keywords: epidemiology of GORD; erosive oesophagitis; oesophageal stricture; oesophageal ulcer; hiatus hernia; natural history; pyrosis; reflux oesophagitis